2016
DOI: 10.1103/physrevd.94.066007
|View full text |Cite
|
Sign up to set email alerts
|

Shear viscosity to entropy density ratio in higher derivative gravity with momentum dissipation

Abstract: We investigate η/s in linear scalar fields modified Gauss-Bonnet theory that breaks translation invariance. We first calculate η/s both analytically and numerically and show its relationship with temperature in log-log plot. Our results show that η/s ∼ T 2 at low temperatures. The causality is also considered in this work. We then find that causality violation still happens in the presence of the linear scalar field and we suggest there is a Gauss-Bonnet coupling dependent lower limit for the effective mass of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 78 publications
2
21
0
Order By: Relevance
“…This relation is somehow inspired by the shear viscosity bound proposed by Kovtun, Son and Starinets [50]. But recent developments have shown that the shear viscosity bound can be strongly violated in anisotropic systems and momentum dissipated systems [51][52][53][54][55][56][57][58] (see also [59][60][61][62][63] for discussions on the diffusion bounds ).…”
Section: Introductionmentioning
confidence: 87%
“…This relation is somehow inspired by the shear viscosity bound proposed by Kovtun, Son and Starinets [50]. But recent developments have shown that the shear viscosity bound can be strongly violated in anisotropic systems and momentum dissipated systems [51][52][53][54][55][56][57][58] (see also [59][60][61][62][63] for discussions on the diffusion bounds ).…”
Section: Introductionmentioning
confidence: 87%
“…Note that this result is given in the case without the axionic fields. It may become more complicate due to the introduction of axionic fields [40] and we shall address these problems in future. In this paper, we will take the constraint (7).…”
Section: Gauss-bonnet-axions Theorymentioning
confidence: 99%
“…Moreover, the result is given in the case without the axion fields. It may become more complicated due to the introduction of axionic fields [96]. Near the UV boundary, r → ∞,…”
Section: Review Of Black Brane In Gauss-bonnet-axions Theory With Arbmentioning
confidence: 99%